Oral rapamycin reduces tumour burden and vascularization in Lkb1(+/-) mice. - Robinson, J; Lai, C; Martin, A; Nye, E; Tomlinson, I; Silver, A (2009)
Patients with Peutz-Jeghers syndrome (PJS) are affected by hamartomatous intestinal polyposis and increased risk of cancers in multiple organs caused by germline mutations in the tumour suppressor gene LKB1. Murine models that recapitulate aspects of PJS have been created. Here we examine the therapeutic effect of rapamycin, a macrolide with anti-tumourigenic and anti-angiogenic properties, in reducing tumour incidence in a large cohort of Lkb1(+/-) mice. To study the influence of early intervention, the animals were dosed with rapamycin from the age of 8 weeks, well before the onset of polyposis. These mice continued to receive the drug, which was well tolerated, throughout their lives. At sacrifice, we observed a reduction in gastric tumour burden in the rapamycin-treated mice (p = 0.0001) compared with age- and sex-matched controls. Treated animals also have a lower number of polyps per mouse than controls. In the polyps from the treated mice, phosphorylation of ribosomal p70 S6 kinase was maintained, while the phosphorylation of AKT at serine-473 was elevated, suggesting that mTORC1 function is maintained at this dosage. Despite this, a significant reduction in microvessel density was seen in polyps from the rapamycin-treated mice compared to those from the control mice (p = 5 x 10(-5)), suggesting that the anti-angiogenic effect of rapamycin played a role in polyp reduction. Overall, we demonstrated that prolonged oral administration of rapamycin from an early age is effective in lowering tumour burden in the Lkb1(+/-) mice without evident side effects.